2017
DOI: 10.1108/ijoa-05-2016-1030
|View full text |Cite
|
Sign up to set email alerts
|

Do compositions of board and audit committee improve financial disclosures?

Abstract: Purpose This paper aims to examine the impact of corporate governance practices on the level of financial disclosures made by the Indian firms. This assumes importance in the context of the role of financial disclosures in addressing the agency problem. Design/methodology/approach Financial disclosure score is computed by considering disclosures provided by the generally accepted accounting principles and is the dependent variable. The independent variable – corporate governance score – is an index comprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 79 publications
0
19
0
1
Order By: Relevance
“…The results from the study indicated that ACs decreased earnings management performed by managers and improved FRQ. This was affirmed in a recent study by Haldar and Raithatha (2017), who argued that ACs guarantee better disclosure and prepare entities to present steadfast and robust financial statements. Almaqoushi and Powell (2017) examined the effect of AC indices, firm value and accounting outcomes in the USA.…”
Section: Literature Review and Development Of Hypotheses 21 Audit Committee Attributes And Cosmetic Accountingmentioning
confidence: 90%
“…The results from the study indicated that ACs decreased earnings management performed by managers and improved FRQ. This was affirmed in a recent study by Haldar and Raithatha (2017), who argued that ACs guarantee better disclosure and prepare entities to present steadfast and robust financial statements. Almaqoushi and Powell (2017) examined the effect of AC indices, firm value and accounting outcomes in the USA.…”
Section: Literature Review and Development Of Hypotheses 21 Audit Committee Attributes And Cosmetic Accountingmentioning
confidence: 90%
“…Hasil penelitian Sil et al (2011) menemukan beberapa karakteristik komite audit menempatkan hubungan yang signifikan dengan manajemen laba. Menurut Haldar & Raithatha (2017) komite audit dapat menjamin penyajian laporan keuangan yang lebih baik. Pada penelitian Saleh & Iskandar (2007) pada 548 sampel data laporan tahunan perusahaan di Malaysia, menemukan bahwa keberadaan komite audit independen, intensitas rapat dan keahlian komite audit dapat mengurangi terjadinya praktik manajemen laba.…”
Section: Kajian Literatur Dan Pengembangan Hipotesisunclassified
“…There are a wide variation and fragmentation among corporate governance studies in India across disciplinary fields including finance, corporate governance practices, earning management, firm performance, firm value, and some other issues. Different areas have been investigated with corporate governance such as corporate illegality (Kaur, 2017), financial disclosure (Haldar & Raithatha, 2017), equity (Fruin & Dossani, 2012;Srivastava et al, 2019), internal control disclosure (Ashfaq & Rui, 2019), international competitiveness (Haldar et al, 2016), ownership (Gollakota & Gupta, 2006), quality of financial information (Hundal, 2016), regulatory and market model (Sehgal & Mulraj, 2008), risk reporting (Saggar & Singh, 2017), Satyam failure (Narayanaswamy et al, 2015), stock market volatility and efficiency (Prasanna, 2013), sustainability (Kansil & Singh, 2018) and talent management (Chahal & Kumari, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%